Energy Use in Irrigation - Rang, Phan (2018)
Presentation of the study “Pilot and Demonstration Activity (PDA) Field-Based Research: Quantifying Water and Energy Links in Irrigation for Improved Resource Utilization in Viet Nam”, Phan Rang, December 21, funded by the ADB.